2017
DOI: 10.1186/s13567-017-0433-6
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent infection with porcine reproductive and respiratory syndrome virus and Haemophilus parasuis in two types of porcine macrophages: apoptosis, production of ROS and formation of multinucleated giant cells

Abstract: Porcine reproductive and respiratory syndrome (PRRS) is one of the most significant and economically important infectious diseases affecting swine worldwide and can predispose pigs to secondary bacterial infections caused by, e.g. Haemophilus parasuis. The aim of the presented study was to compare susceptibility of two different types of macrophages which could be in contact with both pathogens during infection with PRRS virus (PRRSV) and in co-infection with H. parasuis. Alveolar macrophages (PAMs) as residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 57 publications
2
15
0
Order By: Relevance
“…The luminol-amplified chemiluminescence is able to detect superoxide anion as well as hydrogen peroxide in the presence of peroxidases ( 28 ). Because decomposition of these reactive oxygen species is catalyzed by the superoxide dismutase and catalase, these two enzymes apparently play an important role in the oxidative stress resistance of G. parasuis observed in our study as well as by other authors ( 20 , 29 , 30 ). Moreover, catalase was identified among the secreted proteins of G. parasuis Nagasaki strain as immunoreactive with G. parasuis anti-Nagasaki convalescent sera ( 31 ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The luminol-amplified chemiluminescence is able to detect superoxide anion as well as hydrogen peroxide in the presence of peroxidases ( 28 ). Because decomposition of these reactive oxygen species is catalyzed by the superoxide dismutase and catalase, these two enzymes apparently play an important role in the oxidative stress resistance of G. parasuis observed in our study as well as by other authors ( 20 , 29 , 30 ). Moreover, catalase was identified among the secreted proteins of G. parasuis Nagasaki strain as immunoreactive with G. parasuis anti-Nagasaki convalescent sera ( 31 ).…”
Section: Discussionsupporting
confidence: 80%
“…Production of reactive oxygen species (ROS) by in vitro infected PAMs was measured using chemiluminescence (CL) assay ( 20 ). After overnight incubation of PAMs in 96-well plates (37°C, 5% CO 2 ), the wells were washed with Hanks’ balanced salt solution (HBSS, Lonza) and luminol-derivative L-012 (Wako Chemicals GmbH) was added to amplify the CL induced by respiratory burst of stimulated PAMs.…”
Section: Methodsmentioning
confidence: 99%
“…This diverse organism is a common inhabitant of the nasopharyx ( Smart et al, 1989 ; Choi et al, 2003 ; MacInnes et al, 2008 ; USDA, 2016 ) but, when sepsis occurs, presents with clinical signs similar to signs observed with S. suis . Like S. suis , G. parasuis may interact with PRRSV to contribute to PRDC ( Kavanova et al, 2017 ), although clear evidence of such an interaction was not observed by Solano et al (1997) . Vaccination of sows with an autogenous G. parasuis vaccine has been shown to reduce offspring nursery mortality (1.4–2.1% monthly mortality for control vs. 0.5–0.9% monthly mortality for vaccinated; McOrist et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…These models only allowed budding as a mechanism for viral particle production from syncytia, assuming that no apoptosis occurs from fused cells [ 158 ]. Recent reports suggest that this may not be the case [ 159 , 160 , 161 , 162 , 163 , 164 , 165 ], depending on the virus; adjustments during model development and fitting can resolve such issues. In their model, Jacobsen and Pilyugin found that an increase in burst size would allow for tumor control.…”
Section: Modeling Specific Mechanisms Of Actionmentioning
confidence: 99%